Human induced pluripotent stem cells (hiPSCs) derived cells reflect tissue specificity found in patients with Leigh syndrome French Canadian variant (LSFC) - Gélinas, Roselle; Lévesque, Chloé; Thompson Legault, Julie; Rivard, Marie-Eve; Villeneuve, Louis; Laprise, Catherine; Rioux, John D. (Frontiers in Genetics, 2024)
Leigh syndrome French Canadian type (LSFC) is a recessive neurodegenerative disease characterized by tissue-specific deficiency in cytochrome c oxidase (COX), the fourth complex in the oxidative phosphorylation system. LSFC is caused by mutations in the leucine rich pentatricopeptide repeat containing gene (LRPPRC). Most LSFC patients in Quebec are homozygous for an A354V substitution that causes a decrease in the expression of the LRPPRC protein. While LRPPRC is ubiquitously expressed and is involved in multiple cellular functions, tissue-specific expression of LRPPRC and COX activity is correlated with clinical features. larger number of patients and controls to not only validate the current observations but also to delve 33 more deeply in the pathogenic mechanisms of LSFC. 34